Using an Interactive Learning Strategy on Students’ Writing Ability of Procedure Text - Nurdiana, Nurdiana; Roswati, Roswati; afrizal, afrizal; Nazri, Nazri; Susanti, Raden Hariyani (Al-Manar, 2025)
This study investigates students' writing ability, both before and after, and the significant difference after using the Interactive Learning Strategy. This study is categorized as pre-experimental, involving one class as a treatment class. For this study, the sample was collected through a purposive sampling technique, which consisted of sixteen students. Eighth-grade students at SMP Negeri 4 Pulau Merbau were involved in this study. Data were analyzed using SPSS version 23. Researchers applied the Wilcoxon signed-rank test to evaluate data. Results showed an extensive difference in the writing skill of students before and after applying the Interactive Learning Strategy, with pre-test gain of 6.25% and post-test gain of 68.0%. Based on the Wilcoxon signed-rank test, it indicates that Ha is acceptable since sig (2-tailed) = 0.000. The decision-making ground for Ha is significant (sig < 0.05), while H0 is significant (sig > 0.05).